Students’ Views on the Use of Duolingo to Support Reading Comprehension - Tasa Salsabilah; Dzul Rachman; Yeni Rahmawati (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2026)
This study investigates students' perceptions of Duolingo as an ICT-based tool for supporting reading comprehension in English as a foreign Language (EFL) education. While prior research has extensively investigated mobile-assisted language learning, fewer studies have analytically explored how Duolingo shapes students' cognitive and affective engagement in reading-related activities within the context of Indonesian higher education. This study employed a mixed-methods methodology with 54 first-semester English Education students at Universitas Muhammadiyah Kalimantan Timur to address this gap. Data were collected through questionnaires and semi-structured interviews and analyzed employing descriptive and thematic techniques. The results indicate that students typically perceive Duolingo as accessible and interesting for reading practice, though its educational efficacy seems constrained by material simplicity and reliance on consistent internet connectivity. The study demonstrates that Duolingo can serve as a supplementary tool rather than a substitute for formal education, highlighting the complex role of gamified mobile platforms in encouraging reading engagement and supporting learner autonomy in EFL contexts